2003
DOI: 10.1002/elan.200390102
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Drops Electrochemical Sensor for Sulfide Ions Detection

Abstract: The design and characteristics of a novel electrochemical system, which uses a drop as a renewable electroanalytical sensor, are described. This article describes the performance of the electrochemical system, the coupling of the experimental arrangement with flow injection technique and a demonstration of its applicability for the measurement of sulfide. The method is based on renewable drops of ferricyanide ions, buffered by borate. The ferrocyanide ions, product of the reaction between ferricyanide and sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…The versatile, economic and very sensitive electrodes are applied for quantification of several organic and inorganic compounds. Stradiotto and co-workers 144 have also used microelectrodes applied to small volumes. An example is shown in Figure 4, where the detection of sulfide ions on renewable drops of ferricyanide ions is obtained on a platinum microelectrode.…”
Section: Amperometric Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The versatile, economic and very sensitive electrodes are applied for quantification of several organic and inorganic compounds. Stradiotto and co-workers 144 have also used microelectrodes applied to small volumes. An example is shown in Figure 4, where the detection of sulfide ions on renewable drops of ferricyanide ions is obtained on a platinum microelectrode.…”
Section: Amperometric Biosensorsmentioning
confidence: 99%
“…An example is shown in Figure 4, where the detection of sulfide ions on renewable drops of ferricyanide ions is obtained on a platinum microelectrode. 144 The potential for use of UME in biological fluids has been dramatically increased with chemical modifications, such as ion-exchange polymers that have made their applicability in biological fluids more viable. 7,15,145,146 The charged membranes are selective for specific ions and reduce the interference of proteins and other materials indigenous to the physiological system.…”
Section: Amperometric Biosensorsmentioning
confidence: 99%
“…The research carried out by Milani et al. demonstrated that a platinum microelectrode and a drop are appropriate for sulfide determinations in electroanalytical systems [97] . Depending upon the sulfide ion oxidation by ferricyanide, they proposed an arrangement for FIA to evaluate sulfide concentration in aqueous solution.…”
Section: Sulfide Sensing Strategies In Controlled Potential Techniquesmentioning
confidence: 99%
“…Nonetheless, even with its low solubility in water, it is difficult to retain the long-term stability of the RTIL thin film. In this study, we report an easy and reliable method to improve the stability of the RTILmodified electrode by preparing a hydrophobic IL polymer film cross-linked between 1-butyl-3-vinylimidazolium hexafluorophosphate ([C 4 Vim][PF 6 ]) and 1,9-di(3-vinylimidazolium)nonane hexafluorophosphate ([C 9 (Vim) 2 ][PF 6 ] 2 ) on the surface of SPCE. A redox mediator, Fe(CN) 6 …”
Section: Doi: 101002/elan201200431mentioning
confidence: 99%
“…Since Fe(CN) 6 3À was proved an effective redox mediator for the electrochemical sensing of sulfide in neutral media [3][4][5][6], the as-prepared Fe(CN) 6…”
Section: àmentioning
confidence: 99%